Metalinguistic abilities and memory in children first and second grade primary from metropolitan Lima - Matalinares Calvet, María (2011)
This research had as purpose to establish a relationship between metalinguistic abilities and memory in students of first and second grade in Metropolitan Lima. A sample of 164 children were assessed, between first and second grades of primary school, both of sexes, whose ages ranged between 6 and 7 years olds, who applied the Metalinguistic Abilities Test by Gomez, Valero, Buades and Perez (adapted to our reality by Panca, 2000) and Digit Span Subtest of the Wechsler Intelligence Scale for Children (WISC III). The results showed a correlation between metalinguistic abilities and memory of children. A positive correlation was found between syllable segmentation, syllable deletion, rhyme detection, join the phonemes and phoneme counting with retention of digits in forward order, and negative correlation between syllable addition and retention of digits in progressive order. Also it was found positive correlations between syllable segmentation, syllable deletion, isolate phonemes, join the phonemes and count phonemes with retention of digits in reverse order. There were differences in metalinguistic abilities and retention of digits in forward and reverse order, depending on the grade of study.